Confocal fluorescence mapping of pH profile inside hydrogel beads (microgels) with controllable internal pH values. (April 2017) - Zhang, Zipei; Zhang, Ruojie; Sun, Quancai; Park, Yeonhwa; McClements, David Julian
Abstract: Hydrogel beads are particularly promising vehicles for the encapsulation, protection, and release of bioactive agents in foods, supplements, and pharmaceuticals. However, most hydrogel beads are highly porous so that their internal pH is typically fairly similar to that of the surrounding solution, which can lead to degradation of encapsulated pH-sensitive bioactives. In this study, hydrogel beads were fabricated with self-regulating internal pH microclimates by encapsulating Mg(OH)2 inside them. This buffer is insoluble at neutral pH, but dissolves under acidic conditions thereby releasing OH − ions that neutralize H + ions. A quantitative fluorescence confocal laser scanning microscopy (CLSM) method was developed to map the local pH inside the hydrogel beads, which was based on trapping a pH-sensitive dye (fluorescein tetramethylrhodamine dextran, FRD) inside the beads. Hydrogel beads were prepared by injecting a solution containing alginate (gelling agent), Mg(OH)2 (buffer) and FRD (pH probe) into another solution containing calcium chloride (cross-linking agent) using a commercial encapsulation unit. The fluorescence CLSM method was then used to detect the pH profile inside the beads after they were exposed to highly acidic simulated gastric fluids (SGF). Before exposure to SGF, the pH profile inside buffer-free beads was fairly uniform (pH 6.8–7.0), whereas the pH at the center of the hydrogel beads was slightly higher than that at the edge for Mg(OH)2 -loaded beads (pH 7.6–7.2). After exposure to SGF, the pH inside buffer-free beads rapidly became highly acidic (around pH 3), whereas the pH inside Mg(OH)2 -loaded beads remained fairly similar to the initial value (around pH 7.5). The CLSM method developed in this work may be useful for quantifying the local pH in other systems, while the buffer-loaded hydrogel beads may be useful for encapsulation of acid-labile bioactives. Graphical abstract: The fluorescent images of hydrogel beads with and without buffer encapsulation after going through stomach phase (Intensity ratio image was taken based on a pH molecule probe). Highlights: Hydrogel beads were fabricated by encapsulating Mg(OH)2 inside them. A quantitative fluorescence method was developed to map pH inside the beads. The pH inside buffer-load beads was around neutral after stomach digestion. The pH inside buffer-free beads changed to acid value after stomach digestion.